Patterns and predictors of relapse in Merkel cell carcinoma: Results from a population-based study. (January 2022) - Joseph, Kurian; Wong, Justina; Abraham, Aswin; Zebak, Julia; Patel, Anushree; Jones Thachuthara, Aoife; Iqbal, Umar; Pham, Truong-Minh; Menon, Anjali; Ghosh, Sunita; Warkentin, Heather; Walker, John; et al.
Highlights: Adjuvant radiotherapy (RT) improved locoregional control and recurrence free survival without impact on MCC-specific survival and overall survival. Adjuvant RT may be avoided in stage I patients with a clear margin of 1–2 cm after surgery and negative Sentinal Lymph Node Biopsy (SLNB), without high-risk factors. Co-morbidity was independently associated with overall survival. Abstract: Background and purpose: Prospective data evaluating the role of adjuvant radiotherapy (RT) for Merkel Cell Carcinoma(MCC) is lacking. To better understand the efficacy of adjuvant RT, a population-based patterns of failure study was conducted. Methods: We identified MCC patients treated from 1988 to 2018. Primary outcome measures were recurrence-free survival (RFS), overall survival (OS) and MCC-specific survival (MCC-SS). Charlson Co-morbidity Index (CCI) was also calculated. Results: 217 patients with mean age 79 (range: 33–96) were analyzed. The median follow-up was 40 months. Treatments were: surgery(S) alone ( n  = 101, 45%) or S + RT ( n  = 116, 55%). Local recurrence (LR) was low in stage I ( n  = 6, 6.5%) with clear margin of ≥1 cm, negative sentinel lymph node biopsy (SLNB) without high-risk factors, irrespective of adjuvant RT. Tumor size ≥ 2 cm (HR:2.95; p  = 0.024) and immunosuppression (HR:3.98; p  = 0.001) were associated with high risk of nodal failure. Adjuvant RT was associated with significant reduction in regional failure (HR:0.36; p  = 0.002). Distant metastases (DM) were infrequent in stage I (4/90) and stage II (4/34), compared to stage III (32/93). Adjuvant RT improved RFS but did not influence MCC-SS and OS. CCI was a significant predictor of OS. Conclusions: Adjuvant RT improved RFS, without impact on MCC-SS and OS. Co-morbidity rather than RT influenced OS. Adjuvant RT may be avoided in stage I patients with negative SLNB and no associated high-risk factors. Prophylactic RNI could be considered in stage II with high risk features, inspite of negative SLNB. Stage III patients benefited from adjuvant RNI, but no impact on prevention of DM.